Literature Review: Manajemen Peserta Didik di Lembaga Pendidikan Islam - Musthafa, Ahmad Irfan; Espihani, Rahmad; Siminto; Najah, Triwid Syafarotun; Fiani, Tuti (Sagita Academia Journal, 2025)
This research aims to discuss student management in Islamic educational institutions. The methodology used in this research is a literature review based on the results of analysis from journals, books, and other literature such as websites and discussion sessions. To find out how students are managed in Islamic educational institutions. Islamic educational institutions are required to be able to understand and learn how to manage and develop the potential of students. So that Islamic educational institutions can develop the competencies or potential of students and also Islamic educational institutions can be a place for students to develop their talents and interests. There are differences between students in the learning process, some students have rapid cognitive development, and some others have slow development. Islamic educational institutions are required to treat all students fairly so that students can maximally develop their potential.